Analysis of early-onset bloodstream infection due to Escherichia coli infection in premature babies. Issue 32 (August 2017) - Chen, I-Lun; Huang, Hsin-Chun; Wu, Chih-Te; Ou-Yang, Mei-Chen; Chung, Mei-Yung; Chen, Chih-Cheng; Suen, Jau-Ling; Hung, Chih-Hsing
Abstract : Abstract: In early-onset bacteremia among preterm neonates, Escherichia coli ( E. coli ) is the main pathogen and can cause a high mortality rate. Thus, the predictive factors of mortality and extended-spectrum β-lactamase (ESBL)-producing E. coli in preterm babies with E. coli early-onset bacteremia were reported. We retrospectively reviewed preterm neonates who had E. coli bacteremia occurring within 3 days after birth between 2004 and 2015. Maternal and perinatal information were collected from their medical records and analyzed by comparing the survival and nonsurvival groups, and also the ESBL-producing and non-ESBL-producing E. coli bacteremia groups. Mann–Whitney U test, Fisher exact test, and multivariate Cox proportional-hazard model were used for statistical analysis. A total of 27 preterm babies had E. coli bacteremia. The overall mortality rate was 55.56% (15 deaths). Five babies had ESBL-producing E. coli . The low systolic blood pressure of <48 mm Hg and low absolute neutrophil count of <2318 cells/mm 3 were the most significant factors in predicting mortality. Moreover, the level of serum alanine aminotransferase was significantly lower in the ESBL-producing E. coli group than that in the non-ESBL-producing E. coli group. Therefore, the lower systolic blood pressure and absolute neutrophil count were the risk factors of mortality in preterm babies with early-onset E. coli bacteremia, and alanine aminotransferase could be a significant factor in predicting ESBL-producing E. coli .